Generate Random Image-Key using Hash Technique - Nidaa F. Hassan; Akbas E. Ali; Teaba Wala Aldeen (Engineering and Technology Journal, 2010)
Random image is very useful to be used as a source for clipping randomnesssession keys in cryptography. In this paper a new algorithm is proposed to generaterandom image .The random image is generated by mixing initialization vector withnormal digital image; the mixing process is applied in the same way as HASHtechnique. A special cryptography algorithm for generating random numbers isused to generate initialization vector. This proposed algorithm is capable ofgenerating random image that can meet security requirements of cryptographicalgorithms.